(untitled) (Research, Society and Development, 2021)
The aim of this study was to identify bacteria belonging to the family Enterobacteriaceae with resistance profile on inanimate surfaces and utensils of sectors from a University Hospital of Pernambuco. Initially, the samples were collected on 25 inanimate surfaces and utensils of the Intensive Care Unit (ICU), Hemodialysis Center and Medical Clinic in 2018. The samples were plated on MacConkey and SS agar and incubated at 35 ± 2 °C for 24 hours. After incubation, they were submitted to biochemical tests to confirm the presence of bacteria to the family Enterobacteriaceae. Subsequently, Klebsiella pneumoniae carbapenemase (KPC) was identified by the disc diffusion method, as well as by Hodge test; extended-spectrum beta-lactamase producing bacteria (ESBL) by the disk diffusion and double disk diffusion tests; and metallo-beta-lactamase producing bacteria (MBL) through the disc diffusion method according to the Clinical and Laboratory Standards Institute (CLSI). Eight surfaces or utensils of the 18 samples with Enterobacteriaceae presented resistance profile (44.4%). KPC was identified in 46.7% of the samples that presented bacteria with resistance profile, one presented simultaneously KPC and ESBL (6.65%), another one KPC and MBL concomitantly (6.65%) and 6 samples presented only ESBL (40%). Medical Clinic and Hemodialysis Center had the highest presence of resistant Enterobacteriaceae. The detection of resistant microorganisms in hospitals is worrying and emphasizes the importance of health professionals in acquiring knowledge about preventive measures to minimize hospital infections.